1991
DOI: 10.1016/s0886-3350(13)80856-5
|View full text |Cite
|
Sign up to set email alerts
|

Optical quality testing of monofocal intraocular lens implants with a 3 mm and a 4 mm aperture

Abstract: The optical quality of 81 monofocal poly(methyl methacrylate) intraocular lenses (IOLs) from eight U.S. firms was tested using a 3 mm aperture, as recommended by the American National Standards Institute Z80.7 standard for IOLs, and a 4 mm aperture. The use of the larger aperture had no effect on the measurements of refractive power and astigmatism. When examined with the 3 mm aperture, the average resolving power of the IOLs was 81% of the diffraction limit; when examined with the 4 mm aperture, the average r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…One of the reasons that ZMB00 and ZCB00 have similar visual quality in this study may be that we measured the objective visual quality under 4.0 mm pupil diameter. Under 4 mm pupil, the corneal aberration would not affect the results much, and this may be similar to the real optical quality of the IOLs19 26 27; 4 mm is the pupil diameter under natural light during daytime when patients after cataract surgery most frequently use their eyes. The optical quality larger than 4 mm pupil is also important; however, we need to dilate the patient’s pupil, and it is not the natural physiological condition.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…One of the reasons that ZMB00 and ZCB00 have similar visual quality in this study may be that we measured the objective visual quality under 4.0 mm pupil diameter. Under 4 mm pupil, the corneal aberration would not affect the results much, and this may be similar to the real optical quality of the IOLs19 26 27; 4 mm is the pupil diameter under natural light during daytime when patients after cataract surgery most frequently use their eyes. The optical quality larger than 4 mm pupil is also important; however, we need to dilate the patient’s pupil, and it is not the natural physiological condition.…”
Section: Discussionmentioning
confidence: 56%
“…We found no significant differences in objective optical parameters obtained using objective quality analysis system, such as OV 100%, OV 20%, OV 9%, SR and MTF cut-off frequency, indicating that except at all-distance vision, ZMB00 showed greater objective optical quality under 4 mm pupil diameter (representing daytime visual quality) 19 26 27. Most studies showed that OQAS has good intraobserver repeatability, there were still few documents reported it had limitation, especially in eyes with high aberration or poor optical quality 13 14 28–30.…”
Section: Discussionmentioning
confidence: 77%
“…Methods for objective evaluation of optical quality 9-12 include measurement of the eye's aberrations with a wavefront aberrometer, 13,14 assessment of retinal images using a double-pass system, 9,15,16 evaluation of corneal topography, and biometry of the eye. 17 The in vitro optical quality associated with IOLs has also been assessed, [18][19][20] although there are fewer published studies because specific instrumentation is required. Thus, IOL manufacturers and research laboratories perform most in vitro evaluations of IOLs.…”
Section: Resultsmentioning
confidence: 99%
“…The instrument has an artificial and variable exit pupil that is controlled by a diaphragm wheel, whose image is formed on the subject's natural pupil plane. In this study, the optical quality measurements were performed using a double-pass symmetrical configuration and a pupil diameter of 4.0 mm, 19 which is a standard size used in clinical double-pass studies. Quantitative information about the optical quality of the artificial eye was obtained from the point-spread function (PSF) recorded with the double-pass system.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, few reports give a comparative optical characterization of some IOLs, [1][2][3][4][5] and in a few cases they are limited to an analysis of the optical quality of the lenses. [6][7][8][9] On the other hand, many clinical studies have evaluated and compared the visual outcomes in large patient populations after lens extraction and IOL implantation. This approach clearly represents an indirect evaluation of the optical properties of an IOL because they are merged in a number of surgical, biological, and individual masking factors, thus requiring hundreds of subjects to reach statistical relevance.…”
mentioning
confidence: 99%